Comparative Analysis of Pollinator Diversity, Abundance, and Foraging Activity Patterns on Fennel (Foeniculum vulgare) and Black Cumin (Nigella sativa) in the Northern Transitional Zone of Karnataka, India - Asritha, Chava; Kambrekar, D. N.; Kandakoor, Subhash B.; Hiremath, S. M.; Ramesha, N. M. (International Journal of Bio-resource and Stress Management, 2025)
This study investigated during rabi, 2021–22 (October-March) at the University of Agricultural Sciences, Dharwad, Karnataka, India to study the diversity and abundance of insect pollinators on fennel (Foeniculum vulgare Miller) and black cumin (Nigella sativa L.). Visual counting method revealed that Hymenoptera was the dominant order across both crops, with Apis florea (little bee) being the primary pollinator, constituting 94.8% of total visitors in fennel and 86.02% in black cumin. In fennel, Coleoptera (3.7%) and Diptera (1.1%) represented minor pollinator groups, while black cumin showed limited Coleoptera presence (1.16%). Pollinator activity in fennel peaked during 1300–1400 h, with maximum visitation occurring at 90% flowering stage (40.53 visitors m-2 5 min-1). Contrastingly, black cumin pollinator activity peaked between 1000-1100 h, with highest visitation during peak flowering (10.53 visitors m-2 5 min-1). Biodiversity indices revealed that black cumin supported higher pollinator diversity (Shannon-Wiener Index: 0.44–0.55; Simpson Index: 0.24–0.29) compared to fennel (Shannon-Wiener Index: 0.19–0.28; Simpson Index: 0.07–0.12). The findings highlight the crucial ecological role of A. florea in both crops while documenting temporal variations in pollinator activity throughout flowering periods. This baseline information on pollinator communities is essential for developing sustainable pollination management strategies for these economically important seed spices.